The case for God - Armstrong, Karen, 1944- (Canada, Vintage Canada, 2009)
Moving from the Paleolithic age to the present, Karen Armstrong details the great lengths to which humankind has gone in order to experience a sacred reality. While noting that the changing face of the world has necessarily changed the importance of religion at both the societal and the individual level, she makes a powerful, convincing argument for drawing on the insights of the past in order to build a faith that speaks to the needs of our dangerously polarized age
pt. 1. The unknown God (30,000 BCE to 1500 CE) -- Homo religiosus -- God -- Reason -- Faith -- Silence -- Faith and reason -- pt. 2. The modern God (500 CE to the present) -- Science and religion -- Scientific religion -- Enlightenment -- Atheism -- Unknowing -- Death of God?-- Epilogue
Includes bibliographical references (pages 379-390) and index
Keywords: God -- History of doctrines; Religious life -- History; God (Christianity) -- History of doctrines; Christian life -- History; Apologetics